2006
DOI: 10.1128/iai.02103-05
|View full text |Cite
|
Sign up to set email alerts
|

LeishmaniaInfection Impairs β1-Integrin Function and Chemokine Receptor Expression in Mononuclear Phagocytes

Abstract: Leishmania spp. are intracellular parasites that cause lesions in the skin, mucosa, and viscera. We have previously shown that Leishmania infection reduces mononuclear phagocyte adhesion to inflamed connective tissue. In this study, we examined the role of adhesion molecules and chemokines in this process. Infection rate (r ‫؍‬ ؊0.826, P ‫؍‬ 0.003) and parasite burden (r ‫؍‬ ؊0.917, P ‫؍‬ 0.028) negatively correlated to mouse phagocyte adhesion. The decrease (58.7 to 75.0% inhibition, P ‫؍‬ 0.005) in phagocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 57 publications
4
38
0
Order By: Relevance
“…Although we cannot yet offer a formal explanation for the inability of CXCR3 to compensate for CCR5 in this process, there does not appear to be any differences in the expression of the adhesion molecules VLA-1, -2, -4, -5, ICAM-1, or PSGL-1 between CXCR3 + and CCR5 + memory T cells in resting mice (data not shown). One possibility is that ligation of CCR5 may promote changes in intergrin affinity that are necessary for lymphocyte arrest within the pulmonary vasculature, but this hypothesis remains to be tested in the context of respiratory infections (Constantin et al, 2000; Mukai et al, 2001; Pinheiro et al, 2006). In addition, it is unclear whether CCR5, or CXCR3, is also important for secondary effector CD8 + T cells to traffic from local lymphoid tissues back to the lung airways during the latter stages of a recall response.…”
Section: Discussionmentioning
confidence: 99%
“…Although we cannot yet offer a formal explanation for the inability of CXCR3 to compensate for CCR5 in this process, there does not appear to be any differences in the expression of the adhesion molecules VLA-1, -2, -4, -5, ICAM-1, or PSGL-1 between CXCR3 + and CCR5 + memory T cells in resting mice (data not shown). One possibility is that ligation of CCR5 may promote changes in intergrin affinity that are necessary for lymphocyte arrest within the pulmonary vasculature, but this hypothesis remains to be tested in the context of respiratory infections (Constantin et al, 2000; Mukai et al, 2001; Pinheiro et al, 2006). In addition, it is unclear whether CCR5, or CXCR3, is also important for secondary effector CD8 + T cells to traffic from local lymphoid tissues back to the lung airways during the latter stages of a recall response.…”
Section: Discussionmentioning
confidence: 99%
“…Infection with Leishmania has been shown to modulate phagocyte functions associated with cell migration such as signaling, spreading, and adhesion to the substrate (Bray, Heikal, Kaye, & Bray, ; De Almeida, Cardoso, & Barral‐Netto, ; Carvalhal et al, ; Pinheiro, Hermida, Macedo, Mengel, & Bafica, ). Some of these studies suggested that Leishmania ‐induced defects in substrate adhesion might facilitate macrophage migration after infection, promoting parasite dissemination in vivo (Carvalhal et al, ; Pinheiro et al, ; Figueira et al, ). However, other authors have reached the opposite conclusion, proposing that infection with Leishmania impairs the ability of macrophages to migrate (Bray et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Sterile 96-well tissue culture plates were coated with ECM proteins diluted in RPMI 1640 (14). After protein coating, 5 3 10 5 neutrophils in RPMI 1640 supplemented medium were added for 1 h at 37˚C and 5% CO 2 .…”
Section: Neutrophil-ecm Activation Assaymentioning
confidence: 99%